2009
DOI: 10.1002/chem.200901433
|View full text |Cite
|
Sign up to set email alerts
|

Michael Addition Initiated Carbocyclization Sequences with Nitroolefins for the Stereoselective Synthesis of Functionalized Heterocyclic and Carbocyclic Systems

Abstract: The synthesis of various heterocycles and carbocycles (tetrahydrofurans, pyrrolidines, cyclopentanes) has been achieved by using new and efficient ionic addition/cyclization sequences. Nitroolefins play an important role in the Michael addition induced ring-closing reactions (MIRC) reported in the present article, with various substituted alcohols, amines, Grignard reactants, or malonate derivatives acting as the nucleophile partner. The optimized cascade reactions were high yielding in most cases and highly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 241 publications
(109 reference statements)
0
8
0
Order By: Relevance
“…In other words, acrylamides are privileged reaction partners acting as formal [1,4]-dipoles in the popular aza-Michael initiated ring closure (aza-MIRC) strategy. 52 Examples occupying this category of domino transformations are the subject of this section.…”
Section: Domino Reactions Triggered By An Aza-michael Additionmentioning
confidence: 99%
“…In other words, acrylamides are privileged reaction partners acting as formal [1,4]-dipoles in the popular aza-Michael initiated ring closure (aza-MIRC) strategy. 52 Examples occupying this category of domino transformations are the subject of this section.…”
Section: Domino Reactions Triggered By An Aza-michael Additionmentioning
confidence: 99%
“…In this context, reaction of nitroalkenes 18 and N-methylprop-2-ynyl amine 19 was investigated by Rodriguez et al for the regio-and distereoselective synthesis of the 3-methylenepyrrolidines 20 via Michael addition/5-exo intramolecular nucleophilic carbocyclization cascade (Scheme 6). 22 Kanger et al demonstrated a new asymmetric synthesis of chiral pyrrolidines 22 with three stereocenters from 4-aminocrotonate 21 and nitroolens 15 in the presence of 10 mol% bifunctional thiourea catalyst Cat-2. 23 The selectivity of the reaction is highly dependent on the substituent on the nitrogen atom of the aminocrotonate.…”
Section: Synthesis Of Five-membered Heterocyclesmentioning
confidence: 99%
“…The Michael Initiated Ring Closure (MIRC) reaction represents a well-designed approach, which has been used extensively for the construction of carbocyclic compounds 1 and small/medium sized nitrogen 2 or oxygen 3 containing heterocyclic compounds. The MIRC strategy can also be achieved through catalyst free one-pot multicomponent reactions 4 which exhibit high atom-economy and selectivity.…”
Section: Introductionmentioning
confidence: 99%